New coronavirus disease 2019 (COVID-19): Is there an impact on male reproductive health - Kh. S. Ibishev; J. O. Prokop (Вестник урологии)
The male reproductive health depends on several factors that can be divided into two main groups: the first group, genetic or hereditary (in particular, Klinefelter syndrome, etc.), the second acquired factors that depend on the person's lifestyle (bad habits, diet), stress, infectious diseases of the genitourinary system, etc. The presence of infectious and inflammatory diseases of the male reproductive system leads to impaired reproductive and endocrine function, significantly reducing the reproductive potential. In the last three years of our time around the world, including Russia, the number of people who have become ill with a new viral infection (COVID-19) caused by the new coronavirus (SARS-CoV-2), which causes dysfunction and has a negative effect on many organs and organs, body systems.The overview of recent publications is devoted to the study of the effect of SARS-CoV-2 on the reproductive health of men. The search was performed using the Medline, PubMed, and EMBASE databases.